Pengaruh Respiratory Muscle Exercises Terhadap Penurunan Sesak Nafas (Dyspnea) Pada Penderita Penyakit Paru Obstruksi Kronik Di Balai Besar Kesehatan Paru Masyarakat (BBKPM) Surakarta - Vitaloka, Astika Galuh; , Isnaini Herawati, S.Fis.,Ftr.,M.Sc; , Maskun Pudjianto, SMPh, M.Kes (2015)
Background: COPD is aimed at classifying disease that have symptoms of air flow resistance in airways. Clinical symptoms of COPD include cough, sputum production,shortness of breath and activity limitations. Shortness of breath in patient with COPD is caused to poor function of inspiratory muscle, increasing ventilation requirement relative, impaired gas exchange, and dynamic compression of the airway and cardiovaskular factors. COPD patients tend to avoid physical activity that ultimately will lead to immobilization, decreased patient relationship with the enviroment and decreased quality of life. One of the pulmonary rehabilitation with respiratory muscle exercises. Objective: to determine the effect of respiratory muscle exercises to decrease shortness of breath (dyspnea) in patients with COPD in BBKPM Surakarta. Methods of study: using a quasi experiment with methods research design one group pre and post test with control design. Respondents in the study were patients at the Center of Lung Health Society (BBKPM) Surakarta and conducted in March-April 2015, with a total sample of 16 people who met the conclusion criteria. Results were analyzed using the Wilcoxon Test and Mann-Whitney Test. The Result:the test of the influence breatness (MMRCS) on respiratory muscle exercises groupshow results using the Wilcoxon Test p = 0.008 < 0.05, and the influence of different test between respiratory muscle exercises group with kcontrol group using the Mann-Whitney Test shows results p = 0.003 < 0.05, which means there is the influence of respiratory muscle exercises to decrease shortness of breath (dyspnea) in patients with COPD. Conclusion: respiratory muscle exercises can affect the decrease shortness of breath in patients with Chronis Obstructive Pulmonary Disease (COPD). Keywords : Respiratory Muscle Exercises, Shortness of Breath (Dyspnea), COPD